The changes in blood pressure, blood velocity, and hemoglobin level in patients with chronic kidney disease during hemodialysis - Abdul-Hassan Mahdi Salih; Saad Mashkoor Waleed; Abdul-Aziz Ahmed Aziz; Yasmeen Ali Hussien (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Chronic kidney disease (CKD) is characterized by abnormal function and structure of the kidney, which occurs for more than 3 months with a decrease in glomerular filtration (less than 60ml/min/1.73 m2) and albuminuria. When the patients reach the state of end-stage renal failure, replacement therapy should be started, and most of these patients require a special procedure. Hemodialysis (HD), performed using the hemodialysis machine, acts as a filter for removal of waste and aqueous products from blood. In 20% of the HD sessions, a drop in blood pressure (BP) may occur due to dialysis. Objective: To measure the effect of HD, BP, blood velocity (BV), and hemoglobin in Iraqi patients with CKD.Method: A cross-sectional study was adopted to assess the effect of HD on blood volume and BP levels in Iraqi patients with CKD. The study was conducted at Al-Hussein Hospital in Thi-Qar province from December 1, 2019 to July 30, 2020, with the participation of 90 patients (50 males and 40 females). They were diagnosed as having CKD and taking regular treatment in addition to dialysis. The patients were divided into five age groups, and their ages ranged between 21 and 70 years. The study protocol included measuring BP with a sphygmomanometer and BV by Doppler study before and after dialysis.Results: This study showed a significant change in BV and BP before and after HD.Conclusion: Hypotension during hemodialysis seems to be common among patients with end-stage renal disease maintained on hemodialysis; thus, adequate monitoring of BP during dialysis process is essential to avoid any complications. It is also important to know at which hour of the dialysis the hypotension occurred to make a dialysis profile by changing the level of electrolyte on the dialysis set and changing the speed of hemofiltration. From the study, it was found that males are more liable to develop CKD. Thus, it is important that males with high risk factor for CKD, especially those with a history of diabetes and hypertension, do frequent follow-ups.